Challenges Faced By the Kenya Ethics and Anticorruption Commission in Implementing the Strategies Recommended By United Nation Convention against Corruption in Kenya - Injene, Grace Kaome; Ngahu, Dr. Catherine (European Journal of Business and Strategic Management, 2016)
Purpose: The purpose of the study was to determine challenges faced by the Kenya Ethics and Anticorruption Commission in implementing the strategies recommended by united nation convention against corruption in Kenya Methodology: The study used the Case Study method and the unit of analysis which was the Ethics and Anticorruption Commission. The study used both Secondary and Primary data. Content Analysis was the tool that was used to analyze the content and information provided by the respondents during the interviews and documentary materials such as EACC reports. Results: Result findings indicated that slow judicial process, political influence hinder the fight against corruption, weak legal framework, slow process of implementing the auditor general reports, lack of prosecution powers by EACC, lack of seriousness in sentencing corrupt individuals and lack of integrity by the Kenyans elect leaders are some of the challenges affecting the commission. Unique contribution to theory, practice and policy: EACC needs to be more aggressive in educating the public on UNCAC and corruption, its negative effects on development. They need to get the support of the public to speak out against corruption and demand accountability from the government (county and national) and leaders